Kubo and the two strings [videorecording (Blu-Ray + DVD)] - Haimes, Marc, 1971-; Butler, Chris, 1974-; Tindle, Shannon; Passingham, Frank; Marianelli, Dario (Universal Pictures Home Entertainment, 2016)
A young boy named Kubo must locate a magical suit of armor worn by his father in order to defeat a vengeful spirit from the past.